Addressing Maternal Depression Through Home Visiting: One State's Experience With a Breakthrough Series Collaborative. Issue 4 (16th February 2022) - Fifolt, Matthew; Johnson, Heather H.; Preskitt, Julie; Enlow, Margaret; Tullier, Dianna; Arbour, MaryCatherine
Abstract : Background and Objectives: From 2013 to 2017, a national Breakthrough Series (BTS) collaborative in Maternal, Infant, and Early Childhood Home Visiting programs developed a toolkit that led to improvements in maternal depression outcomes. In 2018, Alabama's home visiting program (First Teacher) aimed to reproduce these impacts with a state-led BTS that enrolled 8 local implementing agencies (LIAs) serving more than 500 families. Methods: LIAs tested changes in practices using Plan-Do-Study-Act cycles and tracked data regarding depression screening, referrals, service access, and symptom improvement via run charts. First Teacher administered a post-collaborative survey to assess LIA team members' satisfaction with their BTS experience. Results: Alabama's BTS resulted in positive shifts in maternal depression referrals, service access, and symptom improvement. Change ideas that supported these shifts included the use of a screening script, motivational interviewing, "Mothers and Babies, " and a registry. LIAs noted that BTS tools and resources helped build capacity to address the difficult and frequently stigmatized topic of maternal depression. Conclusion: Findings from this study indicate that evidence- and experience-based practices regarding maternal depression screening, referrals, and service access can lead to symptom improvement among mothers enrolled in a state-based home visiting program. Results of this investigation corroborate findings from previous studies while also incorporating feedback from LIAs about the BTS experience.